2017
DOI: 10.1002/hed.24749
|View full text |Cite
|
Sign up to set email alerts
|

Chondroradionecrosis of the larynx: 24‐year University of Wisconsin experience

Abstract: The diagnosis of CRN is challenging, and the likelihood of successful resolution is modest. A high premium should be placed on efforts directed at prevention, such as tobacco and alcohol cessation. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1189-1194, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The clinical diagnosis of CRN is challenging as RT‐induced changes of the larynx may mimic tumour . Therefore, definitive diagnosis should always integrate a clinical assessment, PET imaging and histopathological diagnosis . In our cohort, the initial T stage was somewhat higher in patients with tumour than in those with radionecrosis.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The clinical diagnosis of CRN is challenging as RT‐induced changes of the larynx may mimic tumour . Therefore, definitive diagnosis should always integrate a clinical assessment, PET imaging and histopathological diagnosis . In our cohort, the initial T stage was somewhat higher in patients with tumour than in those with radionecrosis.…”
Section: Discussionmentioning
confidence: 89%
“…In our cohort, the median ORN onset was 5 months after RT, and the bone most commonly affected was the mandible (20/21 patients). Compared to ORN, Gessert et al reported CRN to occur within a longer time interval after RT . The clinical diagnosis of CRN is challenging as RT‐induced changes of the larynx may mimic tumour .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management includes voice rest, humidification, antibiotics, steroids, hyperbaric oxygen, supportive surgery (tracheotomy, gastrotomy tube placement), debridement, and laryngectomy. 2 Cartilage and bone can generally withstand large doses of RT without gross change in tissue. However, histopathologic studies suggest subclinical CRN can occur in rates as high as 27% of larynges previously irradiated for advanced stage laryngeal SCC.…”
mentioning
confidence: 99%
“…1 Reported risk factors for the development of laryngeal CRN include ongoing smoking, laryngeal trauma, and tumor cartilage invasion. 2 Typically, CRN manifests with a variety of presenting symptoms including weight loss, hoarseness, odynophagia, dysphagia, laryngeal edema, and upper airway obstruction. 2 Clinical features and imaging can be useful in diagnosis, but definitive diagnosis requires biopsy.…”
mentioning
confidence: 99%